BETWEEN SOCIAL HUMANISM AND SOCIAL MOBILIZATION: The Dual Role of Madrasah in the Landscape of Indonesian Islamic Education (JOURNAL OF INDONESIAN ISLAM, 2017)
This article analyzes the dual as well as overlapping role of madrasah in the history of Indonesian Islamic education. It argues that madrasah has long been playing the double roles at once; on the one hand it has served as the enlightening process of Indonesian Islam by giving a sense of moderation. It also has paved the way for the accommodation of non-religious subjects within its existing religious ones. In this sense, madrasah has played its social humanism. Madrasah, however, has been an effective means of power struggle as well as social mobilization among Muslims into the center of socio-political spheres. As Indonesian Muslims have long been marginalized by non-Islamic schooling system, madrasah has helped them struggle from their marginality through the emancipation and participation programs launched by madrasah. Muslims have been incessantly fought for their equality in terms of madrasah’s legal status and demanded more equal treatment from the state. In effect, the enactment of the Law No. 2/1989 marks a radical shift in the direction of Islamic education in Indonesia which is celebrated by the community of madrasah as a new era for their autonomy and equal status before the state.